Heart Failure, Left Ventricular Remodeling, and Circulating Nitric Oxide Metabolites. Issue 10 (14th October 2016) - Chirinos, Julio A.; Akers, Scott R.; Trieu, Lien; Ischiropoulos, Harry; Doulias, Paschalis‐Thomas; Tariq, Ali; Vasim, Izzah; Koppula, Maheswara R.; Syed, Amer Ahmed; Soto‐Calderon, Haideliza; Townsend, Raymond R.; Cappola, Thomas P.; et al.
Abstract : Background: Stable plasma nitric oxide (NO) metabolites (NOM ), composed predominantly of nitrate and nitrite, are attractive biomarkers of NO bioavailability. NOM levels integrate the influence of NO‐synthase‐derived NO production/metabolism, dietary intake of inorganic nitrate/nitrite, and clearance of NOM . Furthermore, nitrate and nitrite, the most abundant NOM, can be reduced to NO via the nitrate‐nitrite‐NO pathway. Methods and Results: We compared serum NOM among subjects without heart failure (n=126), subjects with heart failure and preserved ejection fraction (HFpEF; n=43), and subjects with heart failure and reduced ejection fraction (HFrEF; n=32). LV mass and extracellular volume fraction were measured with cardiac MRI. Plasma NOM levels were measured after reduction to NO via reaction with vanadium (III)/hydrochloric acid. Subjects with HFpEF demonstrated significantly lower unadjusted levels of NOM (8.0 μmol/L; 95% CI 6.2–10.4 μmol/L; ANOVA P =0.013) than subjects without HF (12.0 μmol/L; 95% CI 10.4–13.9 μmol/L) or those with HFrEF (13.5 μmol/L; 95% CI 9.7–18.9 μmol/L). There were no significant differences in NOM between subjects with HFrEF and subjects without HF. In a multivariable model that adjusted for age, sex, race, diabetes mellitus, body mass index, current smoking, systolic blood pressure, and glomerular filtration rate, HFpEF remained a predictor of lower NOM (β=−0.43; P =0.013). NOM did not correlate with LV mass, or LV diffuse fibrosis. Conclusions: HFpEF, but not HFrEF, is associated with reduced plasma NOM, suggesting greater endothelial dysfunction, enhanced clearance, or deficient dietary ingestion of inorganic nitrate. Our findings may underlie the salutary effects of inorganic nitrate supplementation demonstrated in recent clinical trials in HFpEF.